Pengaruh Model Pembelajaran Cooperative Meaningful Instructional Design (C-MID) Dalam Pembelajaran IPS Terhadap Hasil Belajar Siswa Di Kelas VIII SMP Negeri 1 Suranenggala Kabupaten Cirebon - Lestari, Ayu; Puspitasari, Ratna; Nurizzati, Yeti (Universitas PGRI Semarang, 2022)
This research is motivated by the low learning outcomes of students, because in learning activities that are still conventional and the low absorption capacity of students makes learning monotonous from time to time. The inaccuracy of the learning model can hinder and affect the low student learning outcomes. This study uses a quantitative research type, using an experimental method with a pre-experimental design type one group pretest-posttest. While the data collection techniques with observation, questionnaires, tests and documentation. Based on the results of the regression hypothesis test, it was obtained that tcount 4.377 ttable 1.697 while the sig(2-tailed) value of 0.00 0.05. So the decision is that Ha is accepted, meaning that there is a significant effect between the cooperative meaningful instructional design learning model and the social studies learning outcomes of class VIII F students at SMP Negeri 1 Suranenggala, Cirebon Regency.